Teaching ESL/EFL in a World of Social Media, Mash‐Ups, and Hyper‐Collaboration. Issue 4 (December 2013) - Kessler, Greg
<x xml:space="preserve">Abstract</x> This article explores the emerging pedagogical potential offered by today's technologies and how understanding the relationship between emerging technology and emerging pedagogy can enhance the teaching of English as a second or foreign language (ESL/EFL). The author begins with an overview of recent developments in the field, focused upon pedagogical practice and computer‐assisted language learning (CALL), and then describes suggestions for incorporating various forms of social and new media within collaborative learning practices. By incorporating these forms of popular communication into language teaching, teachers can promote participation and engagement. They are also able to raise awareness of the benefits of various forms of literacy. The essay concludes with some thoughts about pedagogical and technological developments that teachers might anticipate in the future.